Abundance and Diversity of Mould Inhabiting Muara Layang Estuary Sediment, Bangka Belitung Islands - SEKAR LARASHATI; MUHAMMAD ILYAS (Society for Indonesian Biodiversity, 2009)
Estuary basin is a fertile area which has important role for sustaining many organisms from estuary and sea. Mould andother saprobic microorganisms have important role to decomposing organic material in estuary water. A study on diversity and abundance of mould inhabiting Muara Layang estuary sediment, Bangka Belitung Islands has not been conducted before. The objective of this study is to investigate the abundance and diversity of mould inhabiting Muara Layang estuary sediment, Bangka Belitung Islands. The mould isolation was based on sample dilution method with Rose BengalChloramphenicol Agar mould isolation media. The abundance of mould was counted by measuring the average Colony Forming Unit (CFU)/ml of all mould colonies which grown on isolation media by Total Plate Count (TPC) method. The diversity of isolated mould was identified based on phenotypic characters by observing both of macroscopic and microscopic mould morphology. The result showed that the growth average of mould colonies is about (5-27.5) x102 CFU/mL. The result of mould identification showed that eight mould genera, Aspergillus (6 species), Chaetomium, Eupenicillium (3 species), Gliocladium, Paecilomyces, Penicillium (3 species), Scopulariopsis, Trichoderma (3 species), one group identified in class level (Coelomycetes), and three groups of unidentified sterile mould isolates were isolated.Key words: estuary, mould, sediment, abundance, diversity.